Antifungal Activity Of Organically Synthesized Silver Nanoparticles Against Fusarium Incarnatum (Desm.) Sacc., Incitant Of Wilt In Crossandra (Applied Biological Research, 2015)
In this study, we synthesized silver nanoparticles (AgNPs) using  common weed Tridax procumbense and tested its antifungal activity  against Crossandra wilt, caused by Fusarium incarnatum (Desm.) Sacc. AgNPs were synthesized by the reaction of 1.0 mM Ag NO3 and 5% T.  procumbense leaf extract. Synthesized AgNPs were first characterized  and then their antifungal activity assessed against the pathogen at  various concentrations using poisoned food technique. The particle size  analysis using particle size analyzer, ESEM and TEM showed that the  particles size ranged 17-40 nm and well dispersed, spherical with zeta  potential of around 50 mV. AgNPs inhibited mycelial growth at all the  concentrations tested (100 - 800 ppm). Complete mycelial inhibition was  observed at 800 ppm followed by 98% at 700 ppm. Ultra-microscopic  observations revealed that the nanoparticles caused hyphal abnormality  and lysis in F. incarnatum. Further, EDX confirmed the presence of  silver particles in mycelia indicating that AgNPs penetrated fungal  hyphae. These studies confirmed that the method of synthesis is efficient  in production of nanoparticles. Antimicrobial activity study revealed a  high potential of Tridax leaf extract stabilized AgNPs.
Keywords: Ag nanoparticles; antifungal activity; Crossandra; Fusarium incarnatum; Tridox procumbense